Antara Kritik Kapitalisme dan Sosialisme Menuju Sistem Ekonomi Islam yang Berkeadilan: Telaah Pemikiran Ekonomi Muhammad Umer Chapra - Khusnul Lailia; Agus Waluyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine in depth Muhammad Umer Chapra's economic thinking in criticizing the capitalist and socialist systems, as well as highlighting his proposal for an Islamic economic system as a fair alternative. This study uses a qualitative approach with a literature review method, focusing on the analysis of Chapra's works and various literature related to the principles of Islamic economics. The results of the study show that Chapra views the capitalist system as incapable of realizing true prosperity because it is oriented towards the accumulation of material wealth and ignores the dimension of morality. Meanwhile, socialism is considered to restrict individual freedom and hinder the productive motivation of society. As a solution, Chapra proposes an Islamic economic system based on the values of tawhid, justice, and maqāṣid al-syarī‘ah, with the aim of realizing social welfare (maslahah) that harmonizes material and spiritual aspects. Through economic instruments such as zakat, the prohibition of usury, and the strengthening of Islamic financial institutions, Chapra emphasizes the importance of proportional wealth distribution and social responsibility. Chapra's ideas are considered relevant to contemporary economic conditions, especially in addressing issues of social inequality, moral crisis, and the demands of sustainable economic development.